2012
DOI: 10.1095/biolreprod.111.093583
|View full text |Cite
|
Sign up to set email alerts
|

NLRP5 Mediates Mitochondrial Function in Mouse Oocytes and Embryos1

Abstract: Unraveling molecular pathways responsible for regulation of early embryonic development is crucial for our understanding of female infertility. Maternal determinants that control the transition from oocyte to embryo are crucial molecules that govern developmental competence of the newly conceived zygote. We describe a series of defects that are triggered by a disruption of maternal lethal effect gene, Nlrp5. Previous studies have shown that Nlrp5 hypomorph embryos fail to develop beyond the two-cell stage. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 67 publications
4
45
0
2
Order By: Relevance
“…A gene that was present in the DDT and vinclozolin DMR associated genes and ovarian disease associated genes was Pkp4, plakophilins 4 [34,55]. The mRNA genes that were present in the DDT and vinclozolin mRNA genes and ovarian disease associated genes were Nlrp5 and Egr1 [34,56,57]. The Nlrp5 is associated with mitochondrial function in oocytes and embryo [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A gene that was present in the DDT and vinclozolin DMR associated genes and ovarian disease associated genes was Pkp4, plakophilins 4 [34,55]. The mRNA genes that were present in the DDT and vinclozolin mRNA genes and ovarian disease associated genes were Nlrp5 and Egr1 [34,56,57]. The Nlrp5 is associated with mitochondrial function in oocytes and embryo [56].…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA genes that were present in the DDT and vinclozolin mRNA genes and ovarian disease associated genes were Nlrp5 and Egr1 [34,56,57]. The Nlrp5 is associated with mitochondrial function in oocytes and embryo [56]. The Egr1 is associated with granulosa cell apoptosis during atresia through the NF-KB pathway [57].…”
Section: Discussionmentioning
confidence: 99%
“…NLRP5 has a role in preimplantation development, probably by controlling mitochondrial metabolism and cellular localization in ovulated oocytes (Fernandes et al, 2012). NLRP7 was initially identified as a factor involved in the pathogenesis of molar pregnancies, a rare genetic condition associated with appearance of hydatidiform moles (Murdoch et al, 2006;Wang et al, 2009).…”
Section: Mammalian Nlrsmentioning
confidence: 99%
“…A relationship between the SCMC and mitochondria was demonstrated by an interesting work carried out by Fernandes and collaborators [44] that showed that NLRP5 mediates mitochondrial function in mouse oocytes and embryos. They observed that ovulated oocytes lacking Nlrp5 have altered localization of mitochondria: they are scattered throughout the cytoplasm, rather than concentrated in the subcortical layer, and show increased activity in order to sustain the oocyte physiological ATP requirement.…”
Section: Scmc Participation In Mitochondria Redistribution During Matmentioning
confidence: 95%